Standardized organic geochemistry data of sediment core PG1746 from Lake Temje (Yakutia, Russia) - Bernhard Diekmann; Boris K Biskaborn; Gregor Pfalz; Larisa B Nazarova; Dmitry A Subetto; Birgit Heim; Mareike Wieczorek; Luidmila A Pestryakova (PANGAEA, 2024)
This data set is part of a larger data harmonization effort to make lake sediment core data machine readable and comparable. Here we standardized organic carbon data of sediment core PG1746 from Lake Temje (Yakutia, Russia). Lake Temje (62°03' N, 129°29' E) is a thermokarst lake located 13 km east of Yakutsk on the Magane Terrace, west of the Lena River at ca. 208 m a.s.l. The lake is shallow, with a maximum depth of 75 cm and no permanent inflows and outflows. The 3.8 m lake sediment core PG1746 was recovered as part of a joint Russian-German expedition of the Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI, Germany, Potsdam) in cooperation with the North Eastern Federal State University (NEFU, Russia, Yakutsk) to Yakutia in July 2004. Sampling was performed from two connected rubber boats in the central part of Lake Temje at 70 cm water depth with a rod-operated half-tube corer (Russian peat corer: 5 cm in diameter, 100 cm long sampler). Overlapping core sections yielded a 380-cm-long sediment-core sequence. The core sections were described and sampled at 5-cm intervals in the field. One set of subsamples were weighted in wet condition, freeze-dried, and weighed again to estimate the water contents. Weight concentrations in total organic carbon (TOC), total carbon (TC), and total nitrogen (TN) contents have been estimated chromatographically on milled samples, using a Vario™ CNS Elementanalyser. The data were used to calculate the TOC/TN ratio, using a factor of 1.167 to obtain the atomic ratio. Calcium carbonate weight concentrations were calculated from the inorganic carbon contents, the difference between TC and TOC, multiplied by a factor of 8.33 to include the stoichiometric contributions from calcium and oxygen. Inorganic carbon concentrations were below the limit of detection in the middle and upper parts of the sediment core.